Correction to: Rural and Urban Place Renewal in Cross-Sector Partnerships - Dahik Loor, Ana Cristina; Moss, Todd W.; Han, Suho (My University, 2023)
In this article, the affiliation details of authors Todd W. Moss and Suho Han were incorrect. The affiliations should have been: